Creation of A Colloid E-Magazine Oriented Towards Chemical Literacy - Sari Sari; Nurhafizah Nurhafizah; Riri Aisyah; Cucu Zenab Subarkah (CV. Generasi Intelektual Digital (GEN ID), 2024)
This research aims to describe the appearance, validation test results, and feasibility test results of an e-magazine oriented toward chemical literacy on colloidal materials. This media is expected to enhance students' literacy in colloidal materials. The research method used is Design-Based Research (DBR) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The study consists of two main stages: the product development stage, which includes analysis and design, and the product testing stage, which includes validation and feasibility tests. The resulting product is an e-magazine designed to promote chemical literacy on colloidal materials. The validation test was conducted by three experts—lecturers and teachers specializing in materials and media. The average r-calculated values for material, language, and media display aspects were 0.93, 0.97, and 0.98, respectively, indicating that the e-magazine is valid. Subsequently, the product underwent a feasibility test with 15 students who had previously studied colloidal materials. The average feasibility test scores for material, language, and media appearance were 93%, 82%, and 95%, respectively. Based on these results, the e-magazine is deemed suitable as a learning medium.